FAKTOR-FAKTOR PREDIKTIF YANG MEMPENGARUHI KEMAMPUAN MENULIS SISWA SEKOLAH DASAR - Nurholishoh, Yunia; Maharani Efendi, Pitri; Abidin, Yunus (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
One of the language skills that must be mastered by students is writing ability. Writing ability is one of the foundations for students to develop effective written communication skills. However, the reality on the ground shows that not all students are able to master writing skills. The purpose of this research is to show the predictive factors that influence students' writing skills in elementary schools. The research method used is the correlational survey method. This research involved one hundred elementary school studentss. The students were given exercises in the form of free essay writing. Then the students were given a questionnaire to find out the predictive factors that influenced them. The results of the study show that predictive factors do not significantly influence the writing abilities of elementary school students.